Satisfaction Level of Managers of the Educational Process in Morphophysiology Discipline - Vivian Vázquez Martínez; Marta González Debén; Maricel Catellanos Rodríguez; Cristobal Torres González; Ignacio Marrero Silva; Mikhail Benet Rodríguez (Medisur)
Background: to improve the quality of the educational process in Morphophysiology. Objective: to assess the satisfaction level of students, teachers and managers directly involved in the educational process in Morphophysiology. Methods: a methodology validated by experts and supported by quality indicators at individual and group level is applied. It includes surveys for students, teachers and managers and focus group for the analysis of variables such as planning and execution of the process, organizational and functional aspects, organizational environment, management quality and educational work. Results: the indicators that affect the satisfaction level of students and teachers are the quality of lectures and the access to technologies. As for managers, it is the lack of control and advice by specialists and methodologists of the educational process in the faculty. Conclusion: the methodology used allows assessing the satisfaction level of students, teachers and managers as well as determining the factors that affect the quality of the educational process in Morphophysiology.